THE STRATEGY DEVELOPMENT OF SMALL AND MEDUIM ENTERPRISES (SMEs) OF ACCOMMODATION AND FOOD SERVICE IN PHUKET - Anusara Sawangchai; Hiran Prasarnkarn; Noppadol Chanrawang; Wanida Hancharoen; Pipop Somwaythee (Jurnal Manajemen dan Kewirausahaan, 2018)
This research aims to study the problematic conditions of small and medium enterprises, of hotels and food services, to provide a strategy for the development of small and medium enterprises, by providing hospitality and food services in Phuket by using integrated quantitative research which is divided into two phases. The first phase is a study of current problems of small and medium enterprises, accommodation and food services. The second phase is a strategy for the development of small and medium enterprises, accommodation and food services in Phuket by using qualitative research. Pieces of data were collected by the expert in-depth interview. Representatives from all sectors, local and national academics were to summarize information about strengths, weaknesses, opportunities and barriers to SWOT Analysis to find the right strategy and stage the forum. The participant were involved to present a draft strategy for the development of small and medium enterprises in Phuket accommodation and food service industry. The analysis of the data in the first phase of the questionnaire was using the statistical programme to distribute the frequency as a percentage value, average standard deviation and analysis of data in phase 2 by content analysis